2021
DOI: 10.1016/j.molcel.2020.10.040
|View full text |Cite
|
Sign up to set email alerts
|

BUB1 and CENP-U, Primed by CDK1, Are the Main PLK1 Kinetochore Receptors in Mitosis

Abstract: Summary Reflecting its pleiotropic functions, Polo-like kinase 1 (PLK1) localizes to various sub-cellular structures during mitosis. At kinetochores, PLK1 contributes to microtubule attachments and mitotic checkpoint signaling. Previous studies identified a wealth of potential PLK1 receptors at kinetochores, as well as requirements for various mitotic kinases, including BUB1, Aurora B, and PLK1 itself. Here, we combine ectopic localization, in vitro reconstitution, and kinetoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 173 publications
(286 reference statements)
8
99
0
Order By: Relevance
“…A number of proteins, including CENP-U and Bub1, are reported to be Plk1 receptors at centromere/kinetochore (Combes et al, 2017, Lens et al, 2010, Lera et al, 2016, Singh et al, 2021. The functional significance for the role of CENP-U and Bub1 in recruiting Plk1 to kinetochores has been elusive (Kang et al, 2006, Qi et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of proteins, including CENP-U and Bub1, are reported to be Plk1 receptors at centromere/kinetochore (Combes et al, 2017, Lens et al, 2010, Lera et al, 2016, Singh et al, 2021. The functional significance for the role of CENP-U and Bub1 in recruiting Plk1 to kinetochores has been elusive (Kang et al, 2006, Qi et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…While this manuscript was under preparation, a study reported how Cdk1 and Plk1 promote kinetochore recruitment of Plk1 onto Bub1 and CENP-U (Singh et al, 2021). Singh et al mainly used in vitro reconstituted kinetochore to report that binding of Plk1 to CENP-U is strictly dependent on priming Cdk1 activity, which phosphorylates threonine 98 to prime Plk1 binding and, in turn, enhances threonine 78 phosphorylation to create a stable docking configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Ser70) have been reported (Holt et al, 2009), which are not direct Cdk1 sites. Candidate kinases that may be involved include Cdc5/Plk1 and indeed Ame1 Ser52/Ser53 constitute candidate Polo-box binding sites and human CENP-U has been established as a kinetochore receptor for Plk1 (Singh et al, 2021). Biochemical reconstitution of the ubiquitination reaction with purified components in vitro can shed light on the molecular requirements and mechanisms of CCAN phosphorylation and ubiquitination by SCF in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Ser70) have been reported (Holt et al, 2009), which are not direct Cdk1 sites. Candidate kinases that may be involved include Cdc5/Plk1 and indeed Ame1 Ser52/Ser53 constitute candidate Polo-box binding sites and human CENP-U has been established as a kinetochore receptor for Plk1 (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a broader context, a putative LxxIxE motif has been identified in human Bub1 ( Cordeiro et al, 2020 ; Singh et al, 2020 ; Wang et al, 2016 ). While this motif has not been tested functionally, it is interesting that this putative LxxIxE motif is preceded by a PLK1 binding motif and is important for restraining PLK1 activity during SAC activation ( Cordeiro et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%